Effects of Sample Volume on Sensory Perception of Soya Milk - Menaka, S. (Proceedings of Eighth International Conference of Sabaragamuwa University of Sri Lanka, 01 - 03 December 2021, 2021)
Food consumption is involved with complex of dynamic process. Food can be taken into the mouth of an individual in various quantities. The quantity depends on the bite size and the type of utensil used. The amount of food that is taken each time in the mouth is highly variable between consumers to detect its sensory attribute. Sensory perception of food items differ from person to person. Presentation order and preceding samples are known to influence the perception of sensory attributes. The present study was designed to evaluate the effect of sample volume on sensory perception of food. A semi trained panel of fifty subjects were asked to rate some sensory attributes of commercially available soya milk. Stimuli were placed in plastic cups in 10 ml, 20 ml and 35 ml. Participants were allowed to sit comfortable in the sensory booth with appropriate ventilation and lightning. The participants were asked to sip the milk provided and mark the liking on a line scale. The scale ranges between 0 - 100. The panelists were requested to rate the smoothness, sweetness, flavor and after taste characteristics of the plain and flavored soya milk. According to the test, the sweetness perception of the flavored soya milk took more volume to detect the taste. Other characteristics were detected with the less volume of milk presented. From the study it can be concluded that the serving size had no effect on the sensory perception of soya milk except the sweetness perception of flavored soya milk (p=0.02). Intake of food in mouth can be varied with the nature of food, familiarization of food and mental condition of panelists. This study can lead to give a clue to the food processors to determine the bite size of a food product they are producing.
Keywords: Sensory Perception; Soya Milk; Sweetness; Sample Volume